Custos e rendimentos operacionais da extração de madeira de eucalipto com cabo aéreo - Simões, Danilo [UNESP]; Fenner, Paulo Torres [UNESP]; Bantel, Carlos Adolfo [UNESP] (Universidade Federal de Lavras (UFLA), 2010)
This study aimed to technically and economically evaluate the aerial cable in the extraction of eucalyptus wood in mountainous region. The technical analysis comprised a study of time and movements by continuous method and productivity was determined by the volume in cubic meters of wood extracted. Economical analysis comprised operational costs parameters and wood extraction cost. Results referred to effective operational performance. The average cost of extraction of wood was US$ 3.35 per cubic meter with operating performance per effective hour of work of 14.16 m³ h-1.

Objetivou-se, neste trabalho, avaliar técnica e economicamente o cabo aéreo na extração de madeira de eucalipto, em regiões montanhosas. A análise técnica englobou um estudo de tempos e movimentos pelo método de tempo contínuo e a produtividade foi determinada por meio do volume em metros cúbicos de madeira extraída. A análise econômica englobou os parâmetros do custo operacional e custo de extração de madeira. Os resultados referem-se ao rendimento operacional efetivo. O custo médio de extração de madeira foi de US$ 3.35 por metro cúbico, com rendimento operacional médio, por hora efetiva de trabalho, de 14,16 m³ h-1.
Costs and operational performance of eucalyptus wood extraction using aerial cable
Keywords: Custos de produção; Tempos e movimentos; Colheita florestal; Production costs; Times and movement; Timber harvesting